The Influence Of Parents' Socioeconomic Status And Self-Control On The Consumptive Behavior Of Management Study Program Students, Faculty Of Economics And Business, Universitas Muhammadiyah Sumatera Utara - Gunawan, Ade; Febri Andani, Tara (International Journal of Science, Technology & Management, 2022)
This study aims to examine the relationship between the socioeconomic status of parents and self-control on the consumptive behavior of students in the Management Study Program, Faculty of Economics and Business, University of Muhammadiyah North Sumatra. This research is a quantitative research with data collection techniques using a questionnaire. The sample used was 97 students of the Management Study Program, Faculty of Economics and Business, University of Muhammadiyah North Sumatra, this study used stratified random sampling. The data analysis technique used classical assumption test, multiple linear regression, t test, F test, and coefficient of determination. The results of this study are the variables of parents' socioeconomic status and self-control influence the consumptive behavior of students in the Management Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara.